(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
Present Study conducted prospectively to find out relation of working hand and position of knot in the neck in cases of hanging. A total of 390 postmortems were conducted in whole year out of which 35 cases (8.97%) were of hanging. Among these 35 cases 33 individuals were working with right hand. Remaining 2 individuals working with right hand the position of knot on neck were on right side in 15 cases (45.45%), on left side in 11 cases (33.33%), on center of occiput in 5 cases (15.15%) & on front of neck in 2 cases (6%). the result indicate that working hand has no relation with position of knot on neck in cases of hanging. To our knowledge this is first study on this problem.